Checklist of ciliates (Alveolata: Ciliophora) that inhabit in bromeliads from the Neotropical Region - Durán-Ramírez, Carlos Alberto; Dias, Roberto Júnio Pedroso; Mayén-Estrada, Rosaura (Zootaxa, 2020)
Species from almost all classes of ciliates are prone to be found inhabiting bromeliads in the Neotropics, from Mexico to Brazil, and the Antilles. Studies of ciliates recorded from bromeliads have been carried out from few bromeliad species, mainly in tropical forest. We compiled all available data of free living and sessile ciliates from bromeliads, including their geographic distribution and bromeliad identity. We provide a list of 170 ciliate species that have been recorded in 52 epiphytic and terrestrial bromeliad species, distributed in ten Neotropical countries . Most of the species belong to the Classes Oligohymenophorea, Colpodea and Spirotrichea. The largest number of ciliate species has been recorded in Brazil and Mexico. Bromeliothrix metopoides and Glaucomides bromelicola were the two species with the widest geographical distribution, 19 species have been recorded only in Mexico, 11 in the Antillean islands, and 89 only in Southamerica. Free living species prevailed over sessile species, and both represent 2% of the total ciliate species number. Sixteen ciliate species have been recorded only inhabiting in bromeliads. Although bromeliads show a high endemicity, their specificity is low in relation to ciliates.